Pergeseran Penggunaan Ragam Bahasa Formal di Kalangan Mahasiswa dalam Komunikasi Akademik Era Digital : Sebuah Analisis Literasi - Maria Novita; Rosalinda Novita Nona; Yohanista Alventia Eva Saputri; Karmelia Selvina Nona; Hairudin Alias; Yeremias Bardi (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This research is motivated by changes in students' academic communication patterns due to the rapid development of digital technology, which has the potential to affect the consistency of formal language use. In academic literacy, formal language plays a crucial role as a marker of professionalism and the accuracy of scientific communication. This study aims to analyze the shift in formal language use in students' academic communication and identify the factors influencing it in the digital era. The research method used a qualitative approach with a descriptive design. Data were collected through an online questionnaire in the form of open-ended questions to students at the University of Muhammadiyah Maumere who actively use digital media in academic communication. Data were analyzed by grouping respondents' answers and identifying language usage patterns. The results show that students understand the differences between formal and informal language, but their application in digital academic communication is not yet consistent. The shift is characterized by the use of abbreviations, slang, and inconsistencies in linguistic rules influenced by instant communication habits, social environments, and the nature of digital media. These findings emphasize the importance of continuously strengthening formal language literacy and academic communication ethics in higher education